Do Tax Knowledge, Level of Trust, and Religiosity De-termine Compliance to Pay Property Tax? - Sakirin Sakirin; Darwanis Darwanis; Syukriy Abdullah (Universitas Syiah Kuala, 2021)
Objective – This study aims to test the effect of tax knowledge, level of trust and religiosity on taxpayers' compliance in paying property tax (PBB) in Aceh Singkil Regency, Aceh, Indonesia. Design/methodology – The population of this study are all property taxpayers in Aceh Singkil Regency for the year 2018 with a total of 34,000 taxpayers. Non-probability sampling technique was utilized to draw the research sample which results in 396 samples. Primary data was obtained through questionnaires distributed to the respondents and analyzed using multiple linear regression models. Results – The results showed that tax knowledge, level of trust and religiosity affect the compliance of the taxpayers of property tax in Aceh Singkil Regency, Indonesia. Partially, tax knowledge affects the compliance of property tax paying of taxpayers while the level of trust affects the compliance to pay property tax of taxpayers in Aceh Singkil Regency. Nevertheless religiosity does not affect the compliance of paying property tax of taxpayers in Aceh Singkil Regency. The findings of this study interestingly provides an evidence of the lack of role of religion in influencing the tax payers’ compliance towards property tax.